Resveratrol and Myopathy - Bastin, Jean (Nutrients, 2016)
Resveratrol is a natural polyphenolic compound produced by plants under various stress conditions. Resveratrol has been reported to exhibit antioxidant, anti-inflammatory, and anti-proliferative properties in mammalian cells and animal models, and might therefore exert pleiotropic beneficial effects in different pathophysiological states. More recently, resveratrol has also been shown to potentially target many mitochondrial metabolic pathways, including fatty acid β-oxidation or oxidative phosphorylation, leading to the up-regulation of the energy metabolism via signaling pathways involving PGC-1α, SIRT1, and/or AMP-kinase, which are not yet fully delineated. Some of resveratrol beneficial effects likely arise from its cellular effects in the skeletal muscle, which, surprisingly, has been given relatively little attention, compared to other target tissues. Here, we review the potential for resveratrol to ameliorate or correct mitochondrial metabolic deficiencies responsible for myopathies, due to inherited fatty acid β-oxidation or to respiratory chain defects, for which no treatment exists to date. We also review recent data supporting therapeutic effects of resveratrol in the Duchenne Muscular Dystrophy, a fatal genetic disease affecting the production of muscle dystrophin, associated to a variety of mitochondrial dysfunctions, which likely contribute to disease pathogenesis.